African savannas : global narratives & local knowledge of environmental change. - Bassett, Thomas J.; Crummey, Donald (James Currey ; Heinemann, 2003)
African farmers and herders modify landscapes in far more subtle and unexpected ways than commonly depicted in environment and development debates. This interdisciplinary collection uses collaborative research from the major savanna regions which stretch across Africa to make its case. Environmental thinking about Africa is dominated by narratives of degradation and chaos. The contributors demonstrate that the empirical foundations of such long-held views are shaky at best.